Pertanggungjawaban Pidana Pengurus LPD yang Melakukan Penggelapan Dana Nasabah di LPD Desa Sulahan, Kecamatan Susut, Kabupaten Bangli - I Gede Artadi Wira Guna; I Nyoman Sukandia; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2022)
Corruption is the act of someone who enriches or is selfish or a certain group of people in abusing the position that has been given. This is the same as what happened in the embezzlement of funds by one of the administrators of the Tanggahan Peken Traditional Village Credit Institution located in Banjar Tanggahan Peken, Sulahan Village, Susut District, Bangli Regency. This research was conducted to reveal the form of criminal liability of LPD management who embezzled customer funds at LPD Sulahan Village, Susut District, Bangli Regency. This research was conducted using empirical legal research methods and using a legal concept analysis approach which was carried out by understanding legal concepts, views and doctrines that developed in legal science. Sources of data used in the form of primary and secondary data. The collected data were analyzed using the Qualitative Method. From the data that has been analyzed, it is revealed that after the trial the LPD management is required to continue to return the money from the embezzlement of funds that is enjoyed by unscrupulous management, not as a result of the actions of the management which results in a difference of 27 billion.